2018
DOI: 10.1371/journal.pone.0193656
|View full text |Cite
|
Sign up to set email alerts
|

“Before Xpert I only had my expertise”: A qualitative study on the utilization and effects of Xpert technology among pediatricians in 4 Indian cities

Abstract: BackgroundDiagnosing tuberculosis (TB) in children presents considerable challenges. Upfront testing on Xpert® MTB/RIF (‘Xpert’)—a rapid molecular assay with high sensitivity and specificity—for pediatric presumptive TB patients, as recommended by India’s Revised National Tuberculosis Control Program (RNTCP), can pave the way for early TB diagnosis. As part of an ongoing project implemented by Foundation for Innovative New Diagnostics (FIND) dedicated to providing upfront free-of-cost (FOC) Xpert testing to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…It can also ensure new clinicians have confidence in the diagnosis, where a patient moves between health providers. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also ensure new clinicians have confidence in the diagnosis, where a patient moves between health providers. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study spanning four Indian cities, clinicians were interviewed to explore their perspectives on the utility of CBNAAT in children with presumptive TB. [ 17 ] Interestingly, despite CBNAAT being made available free of cost, clinicians diverged in various ways from RNTCP guidance that recommends its use “upfront” as a replacement for smear in children. Instead, some clinicians reported using CBNAAT only after Mantoux and chest X-ray were suggestive; others used it post-smear and in some cases CBNAAT was used only after a trial of empirical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…I thank Stefan Ecks for this point who has written on this issue (Ecks, 2004(Ecks, , 2013. 7 For another example of how different cities with their own particular arrangement of actors and network produce different reactions to GeneXpert, please see McDowell et al (2018). the overworked and underpaid field officers) were tied to not just GeneXpert utilization but also positive diagnosis yielded by that new piece of technology.…”
Section: Art Evidence and Expertisementioning
confidence: 99%
“…It must also be mentioned that this was specific to the landscape of Patna; other cities where the multiple actors have a different relation to each other have resulted in a different pattern on how GX is used. For example, seeMcDowell et al (2018) for how GX was utilized by informal providers in Mumbai.Frontiers in Sociology | www.frontiersin.org…”
mentioning
confidence: 99%
“…In a study carried out in India, the degree of diversity in TB diagnostic approaches reported in children, the author highlights an urgent need for concerted efforts to place GeneXpert early in diagnostic algorithms. This would improve speed of diagnosis, empirical treatment and awareness of drug resistance among TB treatment-naive children 24…”
Section: Introductionmentioning
confidence: 99%